Hydraena bahiana sp. n., a new minute moss beetle (Coleoptera, Hydraenidae) from highlands of Northeast Brazil - Benetti, Cesar J.; Valladares, Luis F.; Delgado, Juan A.; Hamada, Neusa (Zootaxa, 2022)
Hydraena (Hydraenopsis) bahiana sp. nov. is described from Bahia State, Northeast Brazil, based on three specimens collected in pools at the headwater of a stream, 1,705 m. asl. The new species belongs to the Hydraena scintillabella subgroup of the leechi group. Description and diagnostic characters are offered; habitus photographs and line drawings of both male and female genitalia are provided. Habitat and distributional data of the new species are also included.